Projection of Transportation CO₂ Emissions and Local Biogas Potential in Jember Regency - Rusdiana Setyaningtyas; Rohimatush Shofiyah; Kasih Imani Putri Sugiarto; Aida Khoirun Nisa (ECOTON: Ecological Observation and Wetlands Conservation, 2026)
The daily transportation sector is a major source of air pollution and CO2 emissions in Jember Regency, driven by the growth of motorized vehicles and fossil fuel consumption. This study aims to project CO2 emissions from daily transportation and to assess the potential of local biogas as a renewable energy alternative for fossil fuel substitution. A quantitative approach based on secondary data was applied using multi-horizon projections for 2030, 2045, and 2060. Transportation-related CO2 emissions were estimated using the IPCC methodology for mobile combustion, while biogas potential was calculated from organic municipal waste, livestock manure, agricultural and plantation residues, and landfill methane using volatile solids–biochemical methane potential and first-order decay approaches. The results indicate that transportation emissions are projected to increase, while Jember Regency has significant local biogas potential, equivalent to 2.98–3.20 PJ of energy per year, indicating opportunities for partial fossil fuel substitution through a scenario-based approach.